Money, methods, and morals: What are development economists up to? - Anke Hoeffler; Reetika Khera (Review of Development Economics, 2024)
In the highly competitive field of publishing in economics journals, methods often become fads sometimes to the detriment of framing meaningful research agendas and of research ethics. In recent times, empirical work based on primary data collection has gained traction. Randomized controlled trials entail not just primary data collection but also interventions involving human subjects. Field research involving data collection is also expensive, raising a number of concerns. In this special symposium we explore questions of research agendas and research ethics, and argue fo rthe acceptance of broader methodological approaches, greater inclusion in the publication process and for a reflection at the disciplinary level of practices related to field research.
Keywords: 330; development economics; diversity in research; mixed methods; randomized controlled trials; research ethics